2013
DOI: 10.1007/s11164-013-1411-x
|View full text |Cite
|
Sign up to set email alerts
|

Boric acid-catalyzed multi-component reaction for efficient synthesis of 4H-isoxazol-5-ones in aqueous medium

Abstract: The one-pot three-component reaction of aryl aldehydes with hydroxylamine hydrochloride and ethyl 3-oxobutanoate/ethyl 4-chloro-3-oxobutanoate/ ethyl 3-oxo-3-phenylpropanoate in the presence of boric acid, H 3 BO 3 , in water leads to 4H-isoxazol-5(4H)-ones in high yields. The merits of this method are efficiency, simplicity, clean, green, easy work-up, high yields, and shorter reaction times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…It was found that the maximum product yield was obtained after 5 min when the reaction was conducted in the presence of 5 mol% KHP at room temperature (Table 8, entry 1). On the basis of these optimum reaction conditions, a variety of aryl aldehydes were reacted with [114][115][116][120][121][122][123][124][125][126][127][128][129][130][131] Efficient tandem synthesis of a variety of pyran-annulated heterocycles malononitrile (3a) in the presence of KHP in water (Table 8). Both electron-rich and electron-deficient substituted benzaldehydes reacted well and gave excellent product yields in short reaction times.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the maximum product yield was obtained after 5 min when the reaction was conducted in the presence of 5 mol% KHP at room temperature (Table 8, entry 1). On the basis of these optimum reaction conditions, a variety of aryl aldehydes were reacted with [114][115][116][120][121][122][123][124][125][126][127][128][129][130][131] Efficient tandem synthesis of a variety of pyran-annulated heterocycles malononitrile (3a) in the presence of KHP in water (Table 8). Both electron-rich and electron-deficient substituted benzaldehydes reacted well and gave excellent product yields in short reaction times.…”
Section: Resultsmentioning
confidence: 99%
“…If necessary, further purification was performed by recrystallization from hot ethanol to give the desired compounds in high yields. The identities of known products were confirmed by comparison of their spectroscopic data and physical properties with those available in recent papers [114][115][116][120][121][122][123][124][125][126][127][128][129][130][131]. General procedure for preparation of a,b-unsaturated nitriles (19a-w)…”
Section: Generalmentioning
confidence: 88%
See 1 more Smart Citation
“…Essentially, these heterocyclic compounds have been synthesized via a multicomponent condensation reaction of various aldehydes, β ‐keto esters and hydroxylamine hydrochloride in the presence of a catalyst. A number of catalysts have been used in one‐pot multicomponent reactions for the synthesis of isoxazol‐5(4 H )‐one scaffolds including boric acid, citric acid, molecular iodine, KI, Ag/SiO 2 , 4‐( N , N‐ dimethylamino) pyridinium acetate, tetrabutylammonium perchlorate/glycine/sodium oxalate, amine‐modified montmorillonite nanoclay, antimony trichloride, mesolite, DABCO functionalized dicationic ionic liquid, nano‐MgO, sodium silicate pentahydrate, citrus fruit juice, pyridinium p‐ toluenesulfonate, cerium chloride heptahydrate, pyridine, nickel (II) acetate and many more . Also, advanced techniques such as microwave heating, grinding, ultrasonic irradiation and visible light in the presence of sodium acetate in aqueous EtOH have also been reported for the preparation of isoxazol‐5(4 H )‐ones, Although many of these protocols suffer from drawbacks and limitations such as low yields/long reaction times, strongly acidic or basic conditions and the use of toxic reagents, stringent reaction conditions, the use of expensive catalyst, multistep synthetic sequence and difficult work up procedures that restrict their scope in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…A Literature survey shows that many catalyzed methods were reported for the synthesis of various isoxazole derivatives. To mention a few, such protocols employed sodium saccharin [33], ultrasonic irradiation [34], sodium silicate [35], sodium benzoate [36], pyridine [37,38], DABCO [39], CH 3 COONa/UV [40], sodium ascorbate [41], sodium tetraborate [42], sodium sulfide [43], pyridine/UV [44], and boric acid [45] as catalysts. Many of these methods have some limitations and drawbacks, such as use of toxic reagents, strong acidic or basic conditions, costly reagents and catalysts, strict reaction conditions, tedious steps, and low product yields and/or long reaction times, which restrict their scope in practical applications.…”
Section: Introductionmentioning
confidence: 99%